"Everyone needs a class like this": High school students' perspectives on a gay and lesbian literature course - Helmer, Kirsten (Educational Forum, 2015)
This article offers insights on how students experienced and made sense of their learning in a trimester-long high school Gay and Lesbian Literature course. Drawing on questionnaires and interviews that the students completed as part of a larger ethnographic study of this class, the author shows how a queer-themed literature curriculum is relevant for both LGBTQ-identifying and straight-identifying students and contributes to a better school climate.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; identités LGBTQIA2+; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; thématiques; école secondaire; états-unis

Pedagogy and content in sexuality education courses in US colleges and universities - Oswalt, Sara B.; Wagner, Laurie M.; Eastman-Mueller, Heather P.; Nevers, Joleen M. (Sex Education : Sexuality, Society and Learning, 2015)
Most research on sexuality courses in US higher education was conducted in the 1980s and 1990s. Less is known about what is being taught in undergraduate sexuality courses today; this study sought to fill that gap. Reviewing content based on 161 courses (provided by 150 different instructors) from all regions of the USA, this study examined overall descriptions of course content and pedagogical strategies in relation to the academic position of the instructor, region of the country and course enrolment size. Results indicated similar content and pedagogical strategies employed with limited differences based on demographic characteristics. The most commonly taught subjects were sexual orientation (95.0%), communication (93.8%), gender identity (93.2%) and gender roles (93.2%). Most courses included reference to contraception (89.4%), HIV and AIDS (88.2%) and STIs (85.7%). Some notable differences included the fact that tenured or tenure-track instructors were more likely to lecture compared to non-tenure-track instructors, and 100% of courses in the West and Northeast addressed sexual orientation compared to 96% for the Midwest and 85% for the South. Most courses included discussion of pleasure (91.1%) and incorporated sexually explicit content (61.9%). The benefits and challenges of having guidelines for sexuality courses at the university/college level were explored.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; discipline; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; sexualité; systèmes éducatifs; thématiques; éducation sexuelle; états-unis; étude qualitative; étude quantitative